Marine Stewardship Council (MSC) Certification of Arctic Fisheries: Processes and Outcomes - Hønneland, Geir (Arctic Review on Law and Politics, 2020)
Certification according to private sustainability standards (ecolabelling) has become an important addition to public fisheries management in recent years. The major global ecolabel in terms of comprehensiveness and coverage is the Marine Stewardship Council (MSC) Fisheries Standard. Under the MSC Standard, the status of the fishery’s target stocks, its impact on the wider ecosystem and the effectiveness of its management system are assessed. Becoming and remaining certified requires continuous behavioural adaptation from fisheries through a fine-meshed system of conditions attached to certification. In this article, MSC certification of two clusters of fisheries in Arctic waters is discussed, one large- and one small-scale. In the Barents Sea cod and haddock fisheries, the main obstacle to certification has been the fisheries’ impact on endangered, threatened and protected (ETP) species and bottom habitats, and in order to remain certified beyond the first five-year certification period, the fishing companies have had to introduce a number of voluntary measures beyond what is required by law. In the local lumpfish fisheries in Greenland, Iceland and Norway, conditions attached to certification have been related to the effects of these fisheries on seabirds and marine mammals. Here essential parts of a management regime, such as biological reference points and harvest control rules, have come about as a direct result of MSC certification. MSC certification is no panacea, but it seems to have found a niche as a supplement to national legislation and international agreements.